Male and gender-diverse victims of sexual violence in the Rohingya genocide: the selective narrative of international courts - Hospodaryk, Victoria (International journal of transitional justice, 2023)
For the approximately one million Rohingya forced to flee Myanmar since October 2016, unfolding proceedings in both the International Court of Justice (ICJ) and the International Criminal Court (ICC) present potential avenues for securing justice. Yet, for male and gender-diverse victims of sexual violence, whose experiences have historically been overlooked in international criminal law, justice requires recognition of all the crimes committed against them. This article demonstrates that the burgeoning narrative of events constructed in and by both the ICJ and the ICC is one which sidelines the experiences of male and gender-diverse victims of sexual violence. By comparing publicly available filings and decisions of the ICJ and the ICC with reports produced by UN bodies and nongovernmental organizations, and drawing upon insights gained from interviews with lawyers working with the Rohingya, I expose the gaps in the emerging narrative of Rohingya victimization and explain the reasons behind them.